Waiver in the Russian Criminal Process from the Point of View of Standards of European Court of Human Rights - CHEBOTAREVA, Irina N. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
The research deals with the case law of European Court of Human Rights against the Russian Federation on complaints of its citizens regarding violation of Article 6 of European Convention on Human Rights in criminal proceedings when it considers waiver. The author has defined and analyzed both the standards of waiver and the Court’s approaches to the establishment of waiver and the requirements and conditions developed by it. The author’s analysis of the decisions of European Court of Justice in respect of Russia, in which the court considered the legality of waiver in specific criminal cases when the Russian authorities claimed that the Applicant had waived his right, has led to the conclusion about misunderstanding of the Russian law executor of this legal phenomenon. As a result the defects of law enforcement are hidden behind the waiver of one’s right in the Russian criminal process.